Parodi Dalam Karya Deni Junaedi - Albertus Charles Andre Tanama (Ars: Jurnal Seni Rupa dan Desain, 2011)
Parody in Junaedi’s Works of Art. Deni Junaedi is an artist who consistently creates parodical paintings. This paper is written from the idea that it is the postmodernism culture which has brought the contemporary art up into view. It is also in the postmodernism culture where parodical art, including parodical paintings exists as a part of contemporary richness. Junaedi’s passion to produce parodical paintings is interesting to be analyzed through these questions: Why is he attracted to create such works of art?; What message does he want to deliver to his audiences?; How his paintings should be seen from the contemporary art point of view?Keywords:  parodical paintings, postmodernism,contemporary art